2016
DOI: 10.1016/j.gloplacha.2016.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Diagenesis of echinoderm skeletons: Constraints on paleoseawater Mg/Ca reconstructions

Abstract: One of the most profound environmental changes thought to be reflected in chemical composition of numerous geological archives is Mg/Ca ratio of the seawater, which has varied dramatically throughout the Phanerozoic. Echinoderms that today typically form high magnesium calcite skeletons are increasingly being utilized as a proxy for interpreting secular changes in seawater chemistry. However, accurate characterization of the diagenetic changes of their metastable high magnesium calcite skeletons is a prerequis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…Owing to this fact, labeling with enhanced Mn 2+ concentration in seawater proved to be a useful method in studying growth dynamics of some invertebrates, in particular some species of molluscs [ 19 21 ]. With respect to echinoderms, it has been argued that most of them are non-luminescent or reveal light blue zones of intrinsic luminescence [ 12 , 18 , 23 , 27 ] although it has been shown that test plates of some field collected echinoids from offshore environments may also display orange luminescence zoning [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to this fact, labeling with enhanced Mn 2+ concentration in seawater proved to be a useful method in studying growth dynamics of some invertebrates, in particular some species of molluscs [ 19 21 ]. With respect to echinoderms, it has been argued that most of them are non-luminescent or reveal light blue zones of intrinsic luminescence [ 12 , 18 , 23 , 27 ] although it has been shown that test plates of some field collected echinoids from offshore environments may also display orange luminescence zoning [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mg/Ca ratio may be significantly enriched or depleted due to various diagenetic factors (e.g. Dickson, 1995;Gorzelak et al, 2016) High-magnesium calcite of echinoderm biomineral is metastable and tends to transform into low-magnesium polymorph during diagenesis. Only the samples that meet all structural and geochemical criteria of good preservation can be used in further interpretation but even then, a precise assessment of the extent of diagenetic alteration is often difficult to evaluate (Gorzelak et.…”
Section: Discussionmentioning
confidence: 99%
“…al., 2016). For instance, sub-microscale removal of intrastereom organic matrix and internal dissolution-precipitation with some transfer of ions may occur without change of stereom architecture (Gorzelak and Zamora, 2013;Gorzelak et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Among existing proxies, echinoderm skeletal remains have perhaps the highest potential to eventually provide a densely sampled continuous Phanerozoic record of a single proxy. However, the suitability of echinoderms skeletal remains for reconstructing seawater Mg/Ca ratios has been questioned as magnesium concentrations significantly vary within individual skeletons 83 , are dependent on the food source 84 , and do not always mirror expected secular Mg/Ca trends even in very well-preserved specimens 85 .…”
Section: S1 Asi Uncertainty and Componentsmentioning
confidence: 99%